A Large Magma Reservoir Beneath the Tengchong Volcano Revealed by Ambient Noise Adjoint Tomography. Issue 7 (1st July 2021) - Zhao, Y.; Guo, Z.; Wang, K.; Yang, Y. J.
Abstract: The Tengchong volcano (TCV) is a large active volcano system in the southeastern Tibetan Plateau. It is characterized by large‐volume magmatic gas emission, active hydrothermal circulation, and intense volcanic and earthquake activities, posing a threat of near future eruptions. However, there is still no available model of the magmatic plumbing system beneath the volcano system, limiting the quantitative assessments of the eruption hazards. Here, we present a high‐resolution 3D model of the TCV constructed using ambient noise adjoint tomography. Our 3D model reveals a large basaltic magma reservoir with a volume of ∼7, 000 km 3 at depths of 20–35 km, which has a melt fraction of ∼2%–4.5%. Our results suggest that the deep crustal magma reservoir is fed by partial melting in the uppermost mantle and is recharging the shallow magma chambers beneath the TCV. Our results are key to understanding the volcanic activities and assessing future eruption hazards. Plain Language Summary: The Tengchong volcano (TCV) is one of the largest active intraplate volcanoes in southwest China. The unrests of the TCV in recent years have attracted a lot of attention and aroused concerns for the future explosive eruptions. In this study, we present a high‐resolution 3D model of the TCV using an innovative method of ambient noise adjoint tomography. Our results reveal a multi‐layered magmatic plumbing system in the lower crust and uppermost mantle beneath the TCV. The large basaltic magma reservoir in the lower crust has a volume of ∼7, 000 km 3 at depths of 20–35 km and melt fraction of ∼2%–4.5%. Thus, the total of melt volume reaches 140–315 km 3 . The deep crustal magma reservoir is fed by partial melting in the uppermost mantle and is recharging the shallow magma chambers. If such a large volume of melt gets erupted in the future, the lava could cover a huge area, threatening the livelihood of the half million people living nearby. It, therefore, becomes urgent to quantitatively assess and model the potential of future eruptions. Key Points: We present a high‐resolution 3‐D velocity model of the Tengchong volcano (TCV) using ambient noise adjoint tomography We reveal a multi‐level magma system in TCV, that is, a low velocity zone in the uppermost mantle feeds the crustal magma reservoir The lower crustal basaltic magma reservoir has a volume of ∼7, 000 km 3 at depths of 20–35 km with melt fraction of ∼2%–4.5%